Perilaku Pemilih Etnik Batak terhadap Pemilihan Kepala Daerah - Ika Ratna Sari; Warjio Warjio (Politeia: Jurnal Ilmu Politik, 2018)
This article discusses about the relationship of clan/ethnicity in choosing. Ethnic problems / clan similarities are a problem that’s often debated in Indonesia "do people choose based on ethnicity / clan similarity?". These are the questions that we often face. Because most people in Indonesia choose based on one tribe / one clan with the prospective leader. The type of research used in this study is a type of qualitative research that seeks to understand and interpret the meaning of an event. The data used in this study are data derived from library studies and also data from the field obtained by distributing questionnaires or questionnaires to voters in Balige District. From these results, most of the voters in the District of Balige chose the pairs of candidates who were one clan and a kinship with them. This is evident from the results of the voting in this area, where the couple Kasmin Simanjuntak / Liberty Pasaribu were the winners. From the data obtained by the author, the majority of those who chose this pair were subjected to the factors of clan / ethnicity and kinship factors.